Analysis of plant spatial characteristics based on visitors' behavioral preferences--A Case Study of Daming Lake in Jinan - Mi, Hanwen (Technium Sustainability, 2022)
The spatial characteristics of different sites in urban parks can influence the activity patterns and distribution of visitors, and visitors' activity preferences are crucial to the planning and design of urban parks. This paper takes Jinan Daming Lake as the research object; firstly, the distribution and activities of visitors in the park are recorded through behavioral observation and questionnaire; secondly, the accessibility, spatial enclosure, and plant light environment of the park are measured and recorded according to the distribution of visitors; finally, the influence of different plant spatial characteristics on the distribution of visitors' behaviors in the park is analyzed through quantitative methods. Finally, the influence of different plant spatial characteristics on the distribution of visitor behavior in the park was analyzed quantitatively to provide a reference for future renovation and construction of urban parks from the perspective of visitor preferences.